Survey of the Lethal Effect of Ciprofloxacin and Supernatant Isolated from Staphylococcus Aureus under the Stress of Ciprofloxacin on Methicillin-Resistant Staphylococcus Aureus Strains Isolated from Clinical Specimens - Monireh Rahimkhani; Ali Reza Mordadi (Tehran University of Medical Sciences, 2022)
Background and Aim: Staphylococcus aureus is gram-positive coccus that is one of the most important causes of nosocomial infections and cause cutaneous or subcutaneous infections. Among these bacteria Methicillin-resistant Staphylococcus aureus (MRSA) are the most important. The aim of the present study was to investigate the lethal effect of a substance isolated from Staphylococcus aureus under the influence of ciprofloxacin on clinical strains of MRSA. Materials and Methods: In the present study, 83 strains of Staphylococcus aureus isolated from hospitals affiliated to Hamadan University of Medical Sciences and were referred to the research laboratory in faculty of Allied Medical Sciences. Strains of Staphylococcus aureus were identified genotyping and phenotyping by PCR test to prove the presence of mecA gene. Minimums Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were examined on number of MRSA in the presence of ciprofloxacin antibiotic as well as supernatant extracted from Staphylococcus aureus fluid culture medium under ciprofloxacin stress. Results: Diagnostic tests of Staphylococcus aureus, including gram staining, catalase and coagulase tests were performed and all strains were Staphylococcus aureus. In the next step, the strains were genetically tested for confirming methicillin-resistant Staphylococcus aureus, by PCR test and present of mecA gene. All 83 samples had mecA genes and were MRSA. The mean MIC of ciprofloxacin and supernatant for different strains of MRSA were 0.032 mg/ml and 0.02 ml/ml, respectively, and the mean levels of MBC ciprofloxacin and supernatants for different strains of MRSA were 0.064 mg/ml and 0.04 ml/ml, respectively.  Conclusion: The effect of ciprofloxacin and supernatant on the death of stressed bacteria has been confirmed so that after bacterial stress by the antibiotic ciprofloxacin expression of genes related to programmed death was seen in a number of MRSA samples. The MIC and MBC values for MRSA strains in the presence of ciprofloxacin and the supernatant showed similar results, indicating the lethal effect of the protein secreted by cultured staphylococci in the presence of low amounts of ciprofloxacin on the bacteria themselves.